Developing Module ‘Experts in Dulmuluk Performance’ in University Students - ., Nurhayati; Purnomo, M E; ., Subadiyono; Meidarini, S (KnE Social Sciences, 2018)
The aim of this study to produce a module as an effective teaching material used by students of the Indonesian Language and Literature Education Study Program of the Faculty of Teacher Training and Education, Universitas Sriwijaya. This study used a research and development method adapted from Jolly and Bolitho. The result of validation showed that the “Expert in Modern Dulmuluk Performance” module gained a score of 16 from a maximum score of 20 and was categorized as very good. The results of the formative evaluation showed that the developed module was practical, based on small-group results. Then, the field test showed that this module had a potential effect on students’ competence in performing modern Dulmuluk. Therefore, it was categorized as a practical and effective module. Keywords: drama performance, Dulmuluk, module